2012
DOI: 10.1371/journal.pone.0048046
|View full text |Cite
|
Sign up to set email alerts
|

Serum BDNF Concentrations Show Strong Seasonal Variation and Correlations with the Amount of Ambient Sunlight

Abstract: Earlier findings show seasonality in processes and behaviors such as brain plasticity and depression that in part are regulated by Brain-Derived Neurotrophic Factor (BDNF). Based on this we investigated seasonal variation in serum BDNF concentrations in 2,851 persons who took part in the Netherlands Study of Depression and Anxiety (NESDA). Analyses by month of sampling (monthly n’s >196) showed pronounced seasonal variation in serum BDNF concentrations (P<.0001) with increasing concentrations in the spring-sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
3

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 53 publications
1
56
3
Order By: Relevance
“…A recent study showed seasonal variation in serum BDNF concentrations with increasing concentrations in the summer period (Molendijk et al, 2012). Irrespective of allocation month or season of allocation we did not observe differences in serum BDNF or VEGF concentrations in our study.…”
Section: Sample Characteristicscontrasting
confidence: 50%
“…A recent study showed seasonal variation in serum BDNF concentrations with increasing concentrations in the summer period (Molendijk et al, 2012). Irrespective of allocation month or season of allocation we did not observe differences in serum BDNF or VEGF concentrations in our study.…”
Section: Sample Characteristicscontrasting
confidence: 50%
“…In contrast, the emerging seasonal pattern for dopamine brain concentration is characterized by higher levels in fall and lower levels in spring (47,48), that is, with a pattern reminiscent of the annual variations in executive brain response observed in our sample. Similarly, seasonal variation in serum brain-derived neurotrophic factor concentration, a protein involved in learning and the regulation and plasticity of neuronal network, has been reported to undergo annual dynamics leading to higher circulating levels in the fall (49). Whether brain responses to learning tasks would have a similar annual pattern as the brain activity related to a working memory task remains to be investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Season might be a possible confounding factor in reduced brain serotonin turnover following selective serotonin reuptake inhibitor therapy [94] and influences the cortisol response to awakening [95]. Serum BDNF concentrations also show strong seasonal variations and correlations with the amount of ambient sunlight [96]. However, also physical activity is higher on long days (≥ 14 hours daylight) when compared with short days [97].…”
Section: Depression As a Matter Of Darknessmentioning
confidence: 99%